Does broadband Internet affect fertility?. (2nd September 2019) - Billari, Francesco C.; Giuntella, Osea; Stella, Luca
Abstract : The spread of high-speed (broadband) Internet epitomizes the digital revolution. Using German panel data, we test whether the availability of broadband influences fertility choices in a low-fertility setting well known for the difficulty in combining work and family life. We exploit a strategy devised by Falck and colleagues to obtain causal estimates of the impact of broadband on fertility. We find positive effects of broadband availability on the fertility of highly educated women aged 25–45. We further confirm this result using county-level data on total fertility. We show that broadband access significantly increases the share of women reporting home- or part-time working. Furthermore, we find positive effects on time spent with children and overall life satisfaction. Our findings are consistent with the hypothesis that access to broadband allows highly educated women, but not the less educated, to reconcile career and motherhood, which may promote a 'digital divide' in fertility.